Utilizing graphene oxide in cementitious composites: A systematic review. (December 2022) - Murali, Mugineysh; Alaloul, Wesam Salah; Mohammed, Bashar S.; Musarat, Muhammad Ali; Salaheen, Marsail Al; Al-Sabaeei, Abdulnaser M.; Isyaka, Abdulkadir
Abstract: Graphene oxide (GO) is a 2D nanoparticle with dimensions less than 100 nm and acts as nano reinforcement in cementitious composites as a filling, crack-arresting agent, and nuclei for cement hydration. GO can be utilized to improve the microstructure and mechanical properties in a variety of construction and building technology applications. Through a coherent, comprehensive mixed reviewing method, this study seeks to evaluate the research efforts on utilizing GO in cementitious composites and map the research viewpoints from available literature (bibliometric analysis and systematic review). A total of 1437 publications were screened in which 59 articles were selected upon relevancy. Bibliometric mapping is used for keyword occurrence and the tested properties of cementitious composites containing GO. The review finds that the advantage of GO as a reinforcement in cement composite is that it is more effective in controlling crack development and propagation at the nano scale level in contrast to conventional reinforcement. The use of GO in cementitious composites offers many interesting paths and provides a foundation for further optimization in concrete, mortar, engineered cementitious composites, and cement paste. On the other hand, this use has a negative influence on various features of each type of reviewed material. More research is needed to gain a better knowledge of the long-term effects of the mechanical properties and durability of GO-based cementitious composites to promote their wider use in diverse applications in the construction sector. Highlights: GO use to improve the microstructure and mechanical properties. Evaluate the research efforts on utilizing GO in cementitious composites. Comprehensive mixed reviewing method was adopted. GO is effective in controlling crack development and propagation at the nano scale level. Also, provides a foundation for further optimization in concrete.